Efficacy of Various Antidiabetic Agents as Add-On Treatments to Metformin in Type 2 Diabetes Mellitus: Systematic Review and Meta-Analysis. (27th March 2012) - Poolsup, Nalinee; Suksomboon, Naeti; Setwiwattanakul, Wanwaree
Abstract : Background and Aim . Diabetes mellitus is a chronic disease that has a great impact on patients and society. Metformin monotherapy is capable of maintaining a target glycemic control only for a short term. The aim of this study was to determine the efficacy of combination therapy of metformin with any antidiabetic agents in type 2 diabetes mellitus (T2DM) patients. Methods . Reports of randomized controlled trials (RCTs) of combination therapy of metformin with various antidiabetic agents in T2DM failing metformin alone were identified. Results . Eight studies were identified in our paper. Thiazolidinediones (TZDs) were as effective as dipeptidyl peptidase IV inhibitors (DPP IV inhs) in reducing HbA1c value (pooled mean difference −0.03%; 95% CI −0.16 to 0.10%). In comparison between TZDs and sulphonylureas (SUs), TZDs reduced fasting plasma insulin (FPI) more effectively than SUs (pool mean difference −5.72 μU/mL; 95% CI −8.21 to −3.22 μU/mL, P < 0.00001 ), but no significant differences were detected in the effects on HbA1c and fasting plasma glucose (FPG) (pooled mean difference −2.19 mg/dL; 95% CI −11.32 to 6.94 mg/dL, P = 0.64 ). Conclusions . Our study showed that TZDs reduced FPG better than did DPP IV inhs and decreased FPI more than did SUs.